Why the Frantic with Digital Note Taking Apps: a Reconfiguration of Knowledge? - Assis, Paulo de (2023)
This paper explores the persistent fascination with discovering new digital and AI-driven note-taking apps, a phenomenon indicative of the broader reconfiguration of knowledge in the digital age. The proliferation of information, unprecedented in volume and variety, necessitates advanced tools for effective management and comprehension. The study examines the role of AI in transforming how we interact with data, presenting these applications as extensions of our cognitive capabilities. By analyzing the unique functions of various note-taking apps, the paper underscores their importance in navigating the modern knowledge landscape. Ultimately, it highlights the continuous evolution of these tools as essential companions in our quest for understanding an ever-changing world.
Article for general public readership.
FRIS
0
Keywords: MetamusicX:Transdisciplinary Encounters in and Beyond Music